Effect of acupuncture therapy for postoperative gastrointestinal dysfunction in gastric and colorectal cancers: an umbrella review - Wang, Yuhan; Wang, Linjia; Ni, Xixiu; Jiang, Minjiao; Zhao, Ling (Frontiers in Oncology, 2024)
Background Gastrointestinal dysfunction is one of the most common postoperative complications of gastric and colorectal cancers.While acupuncture is a highly promising and effective complementary and alternative treatment for postoperative gastrointestinal dysfunction, evidence-based medical evidence for acupuncture is limited. Therefore, the aim of this study was to evaluate the clinical efficacy of acupuncture for postoperative gastrointestinal dysfunction in gastric and colorectal cancer by summarizing the existing systematic review and meta-analysis. Methods We searched eight databases for relevant systematic review/meta-analyses.The PRISMA 2020 statement was used to evaluate the quality of reporting of the included studies, the AMSTAR 2 scale to evaluate the methodological quality, and the GRADE system was applied to assess the level of evidence. Results A total of six systematic reviews/meta-analyses were included in this study, involving 12 different acupuncture therapies. PRISMA 2020 indicated that the studies all scored between 13-20.5. The AMSTAR 2 evaluations showed that five studies were very low quality and one was low quality. For patients with gastrointestinal dysfunction after gastric cancer surgery, ear acupressure, moxibustion, warm needling, and transcutaneous electrical acupoint stimulation(TEAS) could promote the recovery of gastrointestinal function after surgery. In addition, acupoint application was not superior to standard care for time to first defecation(TTFD) and hospitalization time(HT). For postoperative colorectal cancer patients, electroacupuncture, manual acupuncture, warm needling, ear acupressure, acupoint application improved postoperative gastrointestinal function. In addition, the efficacy of acupressure on TTFD needed to be further demonstrated. Conclusion Acupuncture has a positive impact on postoperative gastrointestinal dysfunction in gastric and colorectal cancer, which can improve gastrointestinal function and shorten the length of hospital stay. However, this conclusion still needs to be treated with caution due to the low quality of reporting, methodological quality, and quality of evidence of the included studies. In addition, the safety and long-term effects of acupuncture therapy need to be further explored.